Exploring the Evolving Roles and Opportunities in the Solar Industry - Manan Prajapati; Uday dedaniya; Jignesh Vidani (International Journal of Global Sustainable Research, 2025)
This paper explores the diverse roles and opportunities within the solar industry by comparing key positions in solar panel installation, energy solutions, financing, and retail. It provides a detailed analysis of five distinct job categories: Solar Sales Executive, Solar Energy Sales Representative, Solar Financing Sales Specialist, Solar Energy Sales Consultant, and Solar Financing Sales Specialist. Each role is examined in terms of responsibilities, required knowledge, skills, certifications, and market demand, highlighting the interdisciplinary nature of the solar industry. The paper also investigates the growing demand for solar professionals as the renewable energy sector expands, emphasizing the increasing importance of solar financing and product expertise in driving industry growth. The findings show that while technical knowledge and customer relationship management remain crucial, specialized skills in financing and energy efficiency are gaining prominence. Additionally, certifications such as NABCEP and financial qualifications are becoming increasingly important for career advancement. This study aims to provide valuable insights for professionals considering a career in the solar industry, as well as for organizations looking to recruit talent in this rapidly evolving field